Does low coping efficacy mediate the association between negative life events and incident psychopathology? A prospective-longitudinal community study among adolescents and young adults. (25th February 2015) - Asselmann, E.; Wittchen, H.-U.; Lieb, R.; Höfler, M.; Beesdo-Baum, K.
Abstract : Aims: To prospectively examine whether negative life events (NLE) and low perceived coping efficacy (CE) increase the risk for the onset of various forms of psychopathology and low CE mediates the associations between NLE and incident mental disorders. Methods: A representative community sample of adolescents and young adults ( N = 3017, aged 14–24 at baseline) was prospectively followed up in up to three assessment waves over 10 years. Anxiety, depressive and substance use disorders were assessed at each wave using the DSM-IV/M-CIDI. NLE and CE were assessed at baseline with the Munich Event List and the Scale for Self-Control and Coping Skills. Associations (odds ratios, OR) of NLE and CE at baseline with incident mental disorders at follow-up were estimated using logistic regressions adjusted for sex and age. Results: NLE at baseline predicted the onset of any disorder, any anxiety disorder, panic disorder, agoraphobia, generalised anxiety disorder, any depression, major depressive episodes, dysthymia, any substance use disorder, nicotine dependence and abuse/dependence of illicit drugs at follow-up (OR 1.02–1.09 per one NLE more). When adjusting for any other lifetime disorder prior to baseline, merely the associations of NLE with any anxiety disorder, any depression, major depressive episodes, dysthymia and any substance use disorder remained significant (OR 1.02–1.07). Low CE at baseline predicted the onset of any disorder, any anxiety disorder, agoraphobia, generalised anxiety disorder, any depression, major depressive episodes, dysthymia, any substance use disorder, alcohol abuse/dependence, nicotine dependence and abuse/dependence of illicit drugs at follow-up (OR 1.16–1.72 per standard deviation). When adjusting for any other lifetime disorder prior to baseline, only the associations of low CE with any depression, major depressive episodes, dysthymia, any substance use disorder, alcohol abuse/dependence, nicotine dependence and abuse/dependence of illicit drugs remained significant (OR 1.15–1.64). Low CE explained 9.46, 13.39, 12.65 and 17.31% of the associations between NLE and any disorder, any depression, major depressive episodes and dysthymia, respectively. When adjusting for any other lifetime disorder prior to baseline, the reductions in associations for any depression (9.77%) and major depressive episodes (9.40%) remained significant, while the reduction in association for dysthymia was attenuated to non-significance ( p -value > 0.05). Conclusions: Our findings suggest that NLE and low perceived CE elevate the risk for various incident mental disorders and that low CE partially mediates the association between NLE and incident depression. Subjects with NLE might thus profit from targeted early interventions strengthening CE to prevent the onset of depression.